DEATH ANXIETY DURING COVID- 19 PANDEMIC: A LITARATURE REVIEW - KEYVAN, Ali; BALCIOĞLU, Aylin; ŞEKER, Gizem (Atlas Journal, 2021)
Throughout human history, there have been many global disasters such as life-threatening wars, climate change and epidemics. Today, the new coronavirus disease known as COVID-19 has been defined as a pandemic by the World Health Organization and has taken its place among these disasters and maintains its global status. The COVID-19 pandemic causes various effects on human psychology as well as its physiological effects with increasing case and death rates. It is thought that the COVID-19 pandemic, which can be seen as a threat to human existence, can be associated with death-related anxiety with many features. At this stage, it is important to consider and focus on the death anxiety experienced during the COVID-19 pandemic through various theories such as existential theory, psychoanalytic theory and terror management theory. This article has been prepared as a review of the literature and current research on the pandemic and death anxiety caused by COVID-19. Due to the insufficiency of national and international studies on death anxiety experienced during the COVID-19 pandemic process, it is aimed to contribute to comprehensive research in this field.